The influence of the enriching additives on the dough structure formation and baked muffins - Самохвалова, Ольга Володимирівна; Касабова, Катерина Рубенівна; Олійник, Світлана Георгіївна (Eastern-European Journal of Enterprise Technologies, 2014)
The records, found in literature sources, were analyzed, and it was found that there are no systemized data on a pastry formation when adding powder enriching additives, different in chemical and grain-size composition. The influence of a wheat germ meal and beet fibers on a pastry formation for muffins was studied. Using these additives with different polysaccharide and grain-size compositions favors an effective dough viscosity, elastic and elasticity modules, plastic viscosity, which are positive for the formation of necessary structural-mechanical properties of baked products. It was found that adding enriching additives under study diminishes the adhesion of pastry for muffins that will promote the reduction of technical losses during kneading and forming dough pieces. These properties provide making high-quality baked products.